Roman Law in Pavle Šeroglić’s Work : (Part One: Reception of Greek law in Roman law, Theory of Law, Property Law, Law of Obligations) - Drakić, Gordana; Stanković, Uroš (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
The article sheds light on the regulations of Roman law appearing in the works of Pavle Šeroglić, the first reviewer of Serbian Civil Code (1844) (The Review of the Civil Code for the Serbian Principality, Promulgated on 25 March 1844 (Pregled Zakonika građanskog za Knjažestvo srbsko, 25. marta 1844. obnarodovanog, published in Bačka vila 4/1845, 114–187), Counterresponse to Response of Mister Miloš Svetić in the Third Linguistic Counterattack (Replika na odgovor gospodina Miloša Svetića u Utuku III. Jezikoslovnome, Novi Sad 1847) and Civil Law in Croatian-Slavonian and Serbian-Banat Military Border (Građansko parvo u c.k. Hrvatsko-slavonskoj i Srpsko-banatskoj Vojničkoj granici, Šeroglić’s undated and unpublished commentary of the General Civil Code, kept in the archival materials of Sremski Karlovci Grammar School in the Archives of Serbian Academy of Sciences and Arts in that town. The provisions of civil law cited by Šeroglić are sorted by similarity with necessary clarifications thereto. This paper, being the first of two sequels of the article related to Šeroglić’s accounts on Roman law, shall shed light on the author’s fragments on is Greek legal transplants in Rome, theory of law, property law and law of obligations, whereas the passages in relation with other branches of Roman law shall be scrutinized in the second follow-up.